Synthesis and characterization of bis(N-benzyl-Nisopropyldithiocarbamato) zinc(II) with bidentate nitrogen ligands: crystal structure of Zn[S2CN (C7H7) (iC3H7)]2(bipy) - Normah Awang,; Ibrahim Baba.,; Y. Farina Abd. Aziz ,; Bohari M. Yamin, (Universiti Kebangsaan Malaysia, 2004)
Two adducts of bis(N-benzyl-N-isopropyldithiocarbamato) zinc(II) with 2,2'-bipyridine and 1,10-phenanthroline have been successfully synthesized and characterized by elemental analysis and spectroscopic studies. The IR spectra of these adducts showed the thioureide band, v(C---- N) which occurred at 1440 and 1438 cm-1 respectively, lower than the parent compound at 1471 cm-1. The 13C NMR spectroscopic data for these compounds showed that the carbon signal from CS2 moiety shifted slightly downfield to 206.6 and 208.5 ppm compared to the parent compound at 205.1 ppm. The single crystal structure of bis (N-benzyl-N-isopropyldithiocarbamato )zinc(II)(bipy) has been determined. The structure of this compound showed monomeric nature with hexacoordination of the metal in a highly distorted octahedral geometry.